Analisis Mikrostruktur dan Performa Aus Baja S45C Dengan Perlakuan Panas pada Suhu 700 °C, 750 °C, dan 800 °C - Supriyanto, Agung; Jamaldi, Agus; Margono, Margono; Nugroho, Budi; Faishal, Afif; Rengga, Fedrian Ahmadthur (Universitas Muhammadiyah Metro, 2025)
This study aims to evaluate the effect of heat treatment with varying temperatures on the hardness, microstructure, and wear resistance of S45C carbon steel. Specimens were heated at temperatures of 700 °C, 750 °C, and 800 °C for 30 minutes, then rapidly cooled using a saltwater medium. Test results indicate that increasing the heat treatment temperature significantly enhances surface hardness, with the highest value recorded at 800 °C. Microstructural observations reveal that martensite phase dominates at high temperatures, contributing to increased hardness and resistance to deformation caused by friction. Wear testing showed a negative correlation between hardness and wear volume, with specimens of higher hardness exhibiting narrower and smoother wear marks. These findings confirm that heat treatment temperature control is a key factor in optimising the surface performance of S45C steel for engineering applications requiring high wear resistance.